HORTICULTURAL, MEDICINAL AND CEREMONIAL PLANTS IN PETIGA VILLAGE, TABANAN BALI PROVINCE - Adiputra, Nyoman (Bumi Lestari, 2014)
Sustainable development is a must for Bali. It is due to the fact that one of the negative impact of development is the change of the land use from agriculture into other functions. As a result most of medicinal plants will be extinct. In another hand there is a trend of people to plant horticultures in their house yards. The main issue: is there any relationship between horticulture and sustainable development? In answering it, a field study was conducted in Petiga Village, Tabanan, Bali Province. Observation and  interview were carried out to respondents consisted of five Balinese farmers who nurse cultivate the horticultural plants for their daily activities. Results show that: 1) there are about 159 kinds of plant totally used as horticultural plants; 2) amongst those plants, about 67 plants belong to the medicinal plants and 80 plants belong to ceremonial plants; 3) number of horticultural plants in every house sampled ranged from 63-94 kinds; 4) the popularity of any horticultural plant is affected by the market’s demand. The conclusion which could be drawn is that the medicinal plants as well as the ceremonial plants are used for horticultural plants. It is due to their wonderful colors, nice stems, flowers or leaves, special odors, economical values and magical values as well. Horticulture could be used as a strategy for preservation and conservation program of the medicinal plants in Bali. It is recommended that for the sustainability, all medicinal plants which exist in Bali should be invented and planted in a form of medicinal plant park.
Keywords: horticulture, medicinal plants, ceremonial plants, sustainable development.